Spectral and Temporal Interrogation of Cerebral Hemodynamics Via High Speed Laser Speckle Contrast Imaging - (:unkn) unknown (My University, 2015)
Laser Speckle Contrast Imaging (LSCI) is a non-scanning wide field-of-view optical imaging technique specifically developed for cerebral blood flow (CBF) monitoring. In this project, a versatile Laser speckle contrast imaging system has been designed and developed to monitor CBF changes and examine the physical properties of cerebral vasculature during functional brain activation experiments. The hardware of the system consists of a high speed CMOS camera, a coherent light source, a trinocular microscope, and a PC that does camera controlling and data storage. The simplicity of the system’s hardware makes it suitable for biological experiments. In controlled flow experiments using a custom made microfluidic channel, the linearity of the CBF estimates was evaluated under high speed imaging settings. Under the camera exposure time setting in the range of tens of micro-seconds, results show a linear relationship between the CBF estimates and the flow rates within the microchannel. This validation permitted LSCI to be used in high frame rate imaging and the method is only limited by the camera speed. In an in vivo experiment, the amount of oxygen intake via breathing by a rat was reduced to 12% to induce the dilation of the vessels. Results demonstrated a positive correlation between the system’s CBF estimates and the pulse wave velocity derived from aortic blood pressure. To exemplify the instantaneous pulsatility flow study acquired at high sampling rate, a pulsatile cerebral blood flow analysis was conducted on two vessels, an arteriole and a venule. The pulsatile waveform results, captured under sampling rate close to 2000 Hz. The pulse of the arteriole rises 13ms faster than the pulse of the venule, and it takes 6ms longer for the pulse of the arteriole to fall below the lower fall-time boundary. By using the second order derivative (accelerated) CBF estimates, the vascular stiffness was evaluated. Results show the arteriole and the venule have increased-vascular-stiffness indices of 0.95 and 0.74. On the other side, the arteriole and the venule have decreased-vascular-stiffness indices of 0.125 and 0.35. Both vascular stiffness indices suggested that the wall of arteriole is more rigid than the venule. The proposed LSCI system can monitor the mean flow over function activation experiment, and the interrogation of blood flow in terms of physiological oscillations. The proposed vascular stiffness metrics for estimating the stroke preliminary symptom, may eventually lead to insights of stroke and its causes.
Keywords: Blood Flow Pulse Wave Analysis; Cerebral Blood Flow Monitoring; High Speed Laser Speckle Contrast Imaging; Vascular Stiffness Index